Capacidades coordinativas básica y su influencia en la ejecución del dribling en niños y niñas de la selección del Mini Básquet Sub-9 cantón Vinces Provincia Los Ríos - Quinto Murillo, Elsa Mayiya (2017)
The investigation "the basic coordinated capacities and their influence in the handling in boys and girls of 10 to 12 years of the Selection of Mini basketball of the school Sub-9 of the Canton Vinces province of Los Ríos in the year 2017", approaches a thematic important, it is not about the activity of the coaches, but also about the set of tasks displayed by the athletes, it is the result criterion. A correct direction of the learning process that plans, organizes, executes and controls in the sporting context. To obtain a result, methods of the theoretical level and of the level of scientific research were used, as well as mathematical and statistical methods, which were applied, the results of the failures that the coaches have in relation to the Use of the exercises were provided. the coordinated capacities for the execution of the dribling, in the investigative activity to be summarized has reached the conclusion of a high scientific and methodological level, which will have a solution to the assumed scientific problem.